The Effect of Counseling on the Pregnant Women's Stress of Covid-19: A Clinical Trial Study - Hamideh Moosavi khosravi; Soodabeh Aghababaei; Farideh Kazemi; Azita Tiznobaik; Shahnaz Kohan (Tehran University of Medical Sciences, 2022)
Objective: Due to the Covid-19 pandemic crisis, which causes stress and threatens health, especially in vulnerable groups including pregnant women, the present study was conducted to determine the effect of individual counseling on the pregnant women's stress of Covid-19. Materials and methods: In this randomized controlled clinical trial, 66 pregnant women in 24 to 28 weeks were randomly divided into two groups of intervention (33 participants) and control (33 participants). At the beginning of the study, both groups completed the questionnaires of demographic information and pandemic related pregnancy test. Then, the intervention was performed in 3 sessions with the interval of one week, in the form of individual counseling by BELIFE method for the experimental group. The control group received only the routine services of the centers. The post-test was performed two weeks after the last consultation session for both groups. Data were analyzed using Stata-13 software. Significance level was considered 0.05. Results: The experimental and control groups were almost homogeneous in terms of quantitative and qualitative demographic variables. Total mean and standard deviation of stress score, before and after the intervention in the experimental group, were 40.27 ± 12.65 and 41.71 ± 1.74, respectively. These numbers in the control group were 33.84 ± 13.08 and 43.84 ± 1.69. Comparing the two groups in terms of stress score which was done after the intervention showed that although the stress score in the experimental group was lower than that in the control group, this difference was not statistically significant (p = 0.39). Conclusion: The results of this study show that although individual counseling for pregnant women was able to reduce the mean scores of stress of Covid-19 in the experimental group, this difference was not statistically significant. Therefore, although the BELIFE individual counseling method for pregnant women, who naturally suffer from pregnancy stress, is an acceptable way to reduce their stress, it is recommended to plan and implement early and more effective interventions for these women because the course of stress is severe in them and has an upward trend during Covid-19 pandemic.